Design of Semi-physics Simulation Training System for Offshore Drilling Electrical Engineers ⁎. Issue 8 (2018) - Qin, Yang; Zuo, Xin; Gao, Xiaoyong; Jiang, Aiguo; Yan, Bo; Lei, Fei
Abstract: As the automatic drilling control system is more widely adopted in the field of offshore oil drilling, the integration of the control system has brought the electrical engineers more challenges to the system troubleshooting. There is an urgent need to propose a low-cost training solution for electrical engineers. Therefore, a semi-physics simulation training system of offshore drilling specifically designed for electrical engineers is addressed in this paper. To maintain high simulation fidelity, driller chairs and PLC controllers are copied and realized from field. Mathematical models are built to simulate both normal and fault state of the drilling control system. Different faults are realized by changing the setting parameters of model or switching between faulty models. Finally, with the help of virtual reality technology, the 3-D environment of drilling operation is realized to improve the vision performance. Moreover, an instructor station subsystem is designed to evaluate trainer's performance. Through this simulation training system, the electrical engineers can not only master drilling control system, but also improve the troubleshooting skill.